Repair of regurgitant bicuspid aortic valves: a systematic approach - Boodhwani, Munir; de Kerchove, Laurent; Glineur, David; Rubay, Jean; Vanoverschelde, Jean-Louis; Noirhomme, Philippe; El Khoury, Gebrine (The Journal of thoracic and cardiovascular surgery, 2010)
Patients with bicuspid aortic valves can present with aortic insufficiency caused by cusp disease or the aortic root pathology. We present our 13-year experience with a functional and systematic approach to bicuspid aortic valve repair. Between 1995 and 2008, 122 consecutive patients (mean age, 44 +/- 11 years) with bicuspid aortic valves underwent non-emergency valve repair for isolated aortic insufficiency (43%), aortic root dilatation (14%), or both (43%). Preoperative echocardiography identified aortic dilatation (n = 75), cusp prolapse (n = 96), and cusp restriction (n = 45) as mechanisms of aortic insufficiency. Raphé repair (n = 98) was performed by shaving (21%) or resection with primary closure (60%) or pericardial patch (18%). Functional aortic annuloplasty was performed using subcommissural annuloplasty (n = 51), ascending aortic replacement (n = 17), or aortic root replacement (n = 54) using a reimplantation (76%) or remodeling technique (24%). There was no operative mortality. Five patients underwent early aortic valve reoperation (3 re-repairs). At discharge, 93% of patients had aortic insufficiency grade 0/1 and 7% of patients had grade 2. Seven additional patients underwent aortic valve reoperation during follow-up (2 re-repairs). Overall survival was 97% +/- 3% at 8 years. At 5 and 8 years follow-up, freedom from aortic valve reoperation was 94% +/- 2% and 83% +/- 5%, respectively, and freedom from aortic valve replacement was 96% +/- 2% and 90% +/- 5%, respectively. Freedom from recurrent aortic insufficiency (>2+) was 94% +/- 3% at 5 years. Freedom from thromboembolism and bleeding was 96% +/- 2% at 8 years. A systematic approach to bicuspid aortic valve repair yields good early and midterm results. Repair of bicuspid valves for aortic insufficiency is a feasible and attractive alternative to mechanical valve replacement in young patients.